States, Markets, Families: Gender, Liberalism and Social Policy in Australia, Canada, Great Britain and the United States - Mahon, Rianne (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "States, Markets, Families: Gender, Liberalism and Social Policy in Australia, Canada, Great Britain and the United States," by Julia S. O'Connor, Ann Shola Orloff and Sheila Shaver.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Gender; International comparisons; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social policy